Secure Password Authentication Procedure Utilizing Vectored Passwoed List in Safe Repository/University of Derby: School of Informatics - Pikrammenos Ioannis A; Tolis Panagiotis (2019)
Abstract, Acknowledgements, Introduction, Related Work, Historical Background, Smart Card, Lightweight Directory Access Control, Active Directory, Kerberos, Literature Review, Smart Card, Lightweight Directory Access Protocol, Naming Model, Information Model, Functional Model, Security Model, Active Directory, Kerberos, Security Features and Threats, Security Over LDAP, Bind Operation, Unbind Operation, Threats over LDAP, Kerberos' Security Features and Threats, Kerberos Password Handling, Threats against Kerberos, Main in the Middle Attack, Dictionary - Brute Force Attack, Advanced Persistent Threat, Social Engineering, Overview of the Proposed Solution, Implementation, LDAP, Active Dictionary, Limitations, Eliminated Threats, Discussion, Future Work, Conclusion, Bibliography, Appendices, List of Abbreviations.